Potential Antioxidant and Anti-Inflammatory Properties of Serum from Healthy Adolescents with Optimal Mediterranean Diet Adherence: Findings from DIMENU Cross-Sectional Study - Giuseppina Augimeri; Angelo Galluccio; Giovanna Caparello; Ennio Avolio; Daniele La Russa; Daniela De Rose; Catia Morelli; Ines Barone; Stefania Catalano; Sebastiano Andò; Cinzia Giordano; Diego Sisci; et al. (MDPI AG, 2021)
During adolescence, health status is influenced by several factors, among which dietary pattern is a crucial element of lifestyle in terms of prevention and treatment of metabolic and chronic diseases. The most studied healthy dietary pattern is the Mediterranean Diet (MD), due to a combination of foods that are rich in antioxidant and anti-inflammatory nutrients. The aim of this study, carried out in healthy adolescents from the DIMENU study, is to assess the adherence to the MD, as well as the dietary nutrient intake and to evaluate the potential antioxidant and anti-inflammatory properties of sera from participants grouped according to the MD score. Using the KIDMED score, as the MD quality index for children and teenagers, we found that the adolescents in this study had an average adherence to the MD (6.71 ± 2.58). Adolescents were clustered into three groups based on their MD adherence. Assessment of quality by 24 h recall revealed higher intakes in polyunsaturated fatty acid (PUFA)/saturated fatty acid (SFA) ratio, dietary fibers, vitamins, and total oxygen radical absorbance capacity (ORAC) in the optimal than in poor MD adherence group. We observed that dietary PUFA/SFA ratio was negatively correlated with serum C-Reactive Protein levels, and total dietary fibers were inversely correlated with Erythrocyte Sedimentation Rate values, while total ORAC was directly correlated with serum glucose concentrations. Interestingly, the reactive oxygen metabolite (ROM) concentrations, determined by the ROM assay, were significantly lower in pooled sera from optimal than poor adherers. Finally, using lipopolysaccharide-stimulated human macrophages, as an in vitro model of acute inflammation, we found a reduced secretion of pro-inflammatory cytokines upon serum treatment from adolescents with optimal respect to medium and poor MD adherence. Our results highlight the anti-inflammatory and antioxidant properties of serum from adolescents with healthy nutrition in terms of adherence to the MD, which may have a positive impact on the prevention of chronic diseases in adulthood.